Susceptibility of Specific HLA DRB1*15 AlleleAmong Chronic Hepatitis B Infected Bangladeshi Patients - Akhter, Rokshana; Afzalunnessa, -; Tabassum, Shahina; Hossen, Murad (Bangladesh Journal of Medical Science, 2019)
Background: The outcome of hepatitis B virus (HBV) infection may be influenced by host factors like Human Leukocyte Antigen (HLA).The expression of HLA genes in peripheral blood mononuclear cells (PBMCs) may reflect the molecular mechanism underlying different HBV infection outcomes. Objective: The purpose of the present study was to explore whether HLA DRB1*15 allele confer susceptibility to chronic hepatitis B infected Bangladeshi patients. Method: This cross sectional study was carried out in the Department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU) during July 2012 to June 2013 for a period of one year.Evaluation of HLA DRB1*15 allele distribution among 30 chronic hepatitis B infected (HBV) Bangladeshi patients compared them with 30 healthy individuals.HLA DRB1*15 allele distribution was detected by conventional PCR followed by agarose gel electrophoresis, using commercial low-resolution DRB1*15 allele polymerase chain reaction sequence specific priming kit. Result: A total of 30 chronic hepatitis B infected (HBV) Bangladeshi patients were evaluated together with 30 healthy controls. The study revealed a significant increase of DRB1*15 allele (46.7% vs 20%; RR= 3.5; X2 = 7.2; P<0.05) compared to healthy controls. This is the first report on HLA DRB1*15 allele associations among chronic hepatitis B (HBV) infected Bangladeshi patients. Conclusion: The present study reveals that HLA DRB1*15 allele was more frequent in chronic hepatitis B infected Bangladeshi patients compared to healthy individuals. Thus, HLA DRB1*15 allele of HLA class II molecules significantly affect the outcome of hepatitis B infection. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.783-788